A comparison between rad-hard float zone silicon diodes as gamma dosimeter in radiation processing (Brazilian Journal of Radiation Sciences (BJRS), 2019)
In this work, we report on the results obtained with rad-hard Standard Float Zone (STFZ) and Diffused Oxygenated Float Zone (DOFZ) silicon diodes in radiation processing dosimetry. The dosimetric probes were designed to operate in the direct current mode, as on-line radiation dosimeter. The irradiation of the samples was performed using a 60Co source with a dose rate of almost 2.4 kGy/h. The current response of each diode was measured as a function of the exposure time in steps from 5 kGy up to 50 kGy to achieve a total absorbed dose of 275 kGy. In this dose range it is observed a significant decrease in the photocurrent generated in both devices due to gamma radiation defects produced in their active volumes. To mitigate this effect, the samples were pre-irradiated with Co-60 gamma rays at 700 kGy. Despite of being less sensitive, these devices presented stable and reproducible current signals with a relative sensitivity decrease of about 19% within the whole range of dose studied. The dose-response curves of the pre-irradiated diodes showed quadratic behavior with correlation coefficient higher than 0.9999 for total absorbed dose up to 275 kGy. The comparison of the FZ and DOFZ responses evidenced that the latter was slightly superior to the first. However, it is important to note that all pre-irradiated diodes can be used as gamma dosimeters in radiation processing applications.